CAN PREGNANT WOMEN RECEIVE COVID-19 VACCINE JABS? AN UPDATE - Hassan, Taimoor (Annals of Allied Health Sciences, 2022)
According to one of the largest trials of its kind reported that COVID-19 vaccinations are safe for women who are pregnant, breastfeeding and contemplating pregnancy. The study contrasted vaccination reactions among those women who were lactating, pregnant and those who were neither. Despite the current findings, it appeared that the advantages of getting COVID-19 vaccinations surpassed the dangers for pregnant and nursing women. According to the Centers for Disease Control and Prevention (CDC), SARS-CoV-2 vaccinations provide protection from life-threatening health crisis. Scientists have compared the experiences of pregnant and breastfeeding women with non-pregnant women after vaccination. A total of 17,525 women who received COVID-19 vaccinations were surveyed in this study. The researchers presented their findings in a research letter published in Journal of the American Medical Association (JAMA). According to their findings, “COVID-19 vaccinations were well accepted by pregnant, nursing, or contemplating pregnancy women”. Dr. Alisa Kachikis, an obstetrician-gynecologist at UW Medicine in Seattle, explained the study to Medical News Today (MNT), which began in January 2021. “When the COVID-19 vaccinations were first rolled out, there was no data on the vaccines in pregnant and lactating women, so we launched the COVID-19 Vaccines in Pregnancy and Lactation Registry,” she explained. “Our prospective, survey-based study then began to collect information on the experiences of pregnant and lactating women, as well as those who were neither pregnant nor lactating but were planning pregnancy”. Study findings owing to Vaccination Three groups were created to study the effects of the COVID-19 vaccination. In the study 7,809 women were pregnant, 6,815 nursing, and 2,901 were neither pregnant nor nursing but planned to get pregnant. These three groups accounted for 44.6%, 38.7%, and 16.5% of the study's population. When the volunteers received their first dose of vaccination, the scientists randomly allocated them to one of three groups. Pfizer-BioNTech BNT162b2 or Moderna mRNA-1273 vaccines were given to the majority of individuals in the study. Approximately 17,005 (97 percent) of the participants experienced side effects following their first dosage. Pain at the injection site and fatigue were the most prevalent side effects. According to studies, the second dose was associated with more severe responses. All groups reacted in the same way, though. Scientists reviewed their data and found that 6,586 women had received second dosage of the vaccination. 16,244 of the patients (94.8 percent) were still pregnant at the time of their second COVID-19 dosage, while 288 (4.3%) had given birth, and 49 (0.7 percent) had experienced a miscarriage. 155 (2.3 percent) lactating women reported interrupted nursing after the first dosage and 130 (2.2 percent) reported it after the second dose. There were also reports of a significant reduction in milk production for less than 24 hours after vaccination. This was detected in 339 (5.0%) subjects after the first dosage, and in 434 (7.2%) after the second dose. What study concluded? The advantages of the COVID-19 vaccination for pregnant and breastfeeding women exceed the dangers, according to the study. Olajumoke Adebayo, a maternal health specialist and young midwife leader at the International Confederation of agrees with this assessment of mother health. There were many questions regarding the effects of vaccinations on pregnant and breastfeeding women, so this [study] is a solid beginning point, Adebayo said. The Pill Club's chief medical officer, Dr. Amy Roskin, reaffirmed the findings: “I'm extremely happy that this study offers more support to important medical groups, including the American Medical Association”. Nevertheless, this study has several drawbacks. The researchers admitted that there may be some bias in it. This is owing to the fact that participants were selected from a suitable sample size, they generally self-reported their emotions, and that they were primarily healthcare workers at the time of the study.